Students’ Perception of the Learner Support Services in Distance Learning Institute (DLI), University of Lagos - Modebelu, Obiageli J.; Adegun, Adedunni O. (NIU Journal of Social Sciences, 2019)
Open distance learning has come to stay as one of the recognized mode of learning at different levels of education especially university level . The main purpose of this study is to determine students’ perception of the learner support services in Distance Learning Institute (DLI), University of Lagos. Specifically, the study sought to ascertain students’ perception of the help desk and counselling services in DLI and find out students’ views about the ICT and LMS services in DLI. 6 Research Questions and 2 hypotheses were raised to guide the study. The study adopted the descriptive survey research design. The population of the study was made up of 10, 889 (5329 male and 5560 female) registered students of DLI for 2016/2017 academic session. Proportionate stratified sampling method was employed to select 386 students for sample size of the study. Mean score and standard deviation (SD) were used to answer the research questions while the t-test was used to test the null hypotheses at 0.05 level of probability. In testing the hypotheses, t-test statistical tool was employed. The results showed that students perceived the help desk is strategically located and the staff are friendly to attend to the students. They also perceived that DLI library is not conducive for learning, the library cannot be accessed on-line and not well equipped with current books. Among the findings were that learners will need the audio and video presentations of the modules, L.M.S need to be upgraded. The hypotheses revealed a significant difference between the perceptions of learner support services by students based on gender with t-test value of 9.901 and p 0.000<0.05. It was evident with t-test value of 4.168, p0.000<0.05, that there is significant difference in the perception of learner support services provided in DLI by the students based on year of study. It was recommended that the counseling centre should be publicized to attract more students. The DLI AIG blog should post information on personal and social issues bothering students. Keywords: Learner support services, Gender, Open and Distance learning, Perception